Biased Behavior And Stock Investment Decisions Of Investors In Bali, Indonesia - Salasa Gama, Agus Wahyudi; Yeni Astiti, Ni Putu; Eka Mitariani, Ni Wayan (MATRIK: JURNAL MANAJEMEN, STRATEGI BISNIS, DAN KEWIRAUSAHAAN, 2023)
Investment decisions are often affected by irrational behavioral factors that cause improper logical analysis. Herding and overconfidence are two behaviors that lead to biased decision-making, specifically regarding investment. Therefore, this study aimed to test the effect of herding and overconfidence on investment decisions moderated by financial knowledge and attitude. Using a sample of 267 stock investors, the test was conducted with PLS-SEM. The results showed that overconfidence positively influences individuals' investment decisions, while herding has no effect. Financial knowledge and attitude were found not to moderate this effect but could act as predictor variables with a significant positive impact on investment decisions.